THE NATURE OF PSYCHOSOCIAL DEVELOPMENT IN EARLY CHILDHOOD ACCORDING TO ERIK ERIKSON'S VIEW - Khairani Khairani; Maemonah Maemonah (Jurnal Kajian Gender dan Anak, 2021)
Humans are living things whose growth and development are studied by many researchers in the world, one of whom is Erik H. Erikson who produced psychosocial theory. Erikson believes that every stage of human development is a specific psychosocial struggle contributing to personality growth.  It means that the stages of one's life from birth to death are formed by social influences that interact with an organism,thus making it mature physically and psychologically. This type of research  uses a type of library research that is used in the collection of information and data in depth through various literature, books, notes, magazines, other references, as well as relevant previous research results, to get answers and theoretical foundations on problems in Erikson's theory, there are 8 stages of development that develop throughout life where each stage consists of Trustt versus disbelief, Autonomiy versus shame’s and doubt, Initiative versus guilt, Hard work versus inferiority, Identity versus identity confusion, Intimacy versus isolation, Generativity versus stagnation, and Integrity versus despair.